PENGEMBANGAN KOMPETENSI GURU MGMP SENI BUDAYA SMP JAKARTA MELALUI PELATIHAN PENYUSUNAN ARANSEMEN MUSIK SEKOLAH MENGGUNAKAN MEDIA DIGITAL - Mifta Firdhani, Aldhila (Program Studi Pendidikan Musik, 2021)
The purpose of this community service is to develop the competence of junior high school art and culture teachers who are members of the MGMP in Jakarta regarding the making of school music arrangement materials in music learning that are easier to play during the covid-19 pandemic. The implementation method is carried out in the form of workshops and training. The implementation is carried out in several stages, namely initial activities in the form of training, core activities in the form of workshops, and FGDs, while the final activity is an independent mentoring activity in the preparation of school music arrangements in various forms that can be used in direct music learning in each participant's class. The data collection instrument was in the form of a participant satisfaction questionnaire with this workshop and training activity. The results of the evaluation conducted by the teacher stated that this activity had a positive impact on the development of professional competence